Determining earthquake epicentre from a single 3-component seismological station - TAID, M.; LYNGDOH, A. C.; GHOSE, A. K. (MAUSAM, 2009)
An attempt has been made in this study to determine the epicentres by trigonometrical method from a single station using the three components of the ground’s motion recorded by the Benioff Short Period Seismograph of the World Wide Standardized Seismograph Network (WWSSN) at Central Seismological Observatory (C.S.O.), Shillong. The trigonometrical method is based on the angle of bearing obtained from the ratio of the amplitudes of waves recorded on the horizontal components of the WWSSN seismograms. A comparison of recorded epicentres from the I.M.D. Seismological Network of Seismo, New Delhi with that of a single station i.e., C.S.O., Shillong has been made to estimate the accuracy of the method. The characteristics of the epicentral variations obtained from the Seismological Network of Seismo, New Delhi with that of C.S.O., Shillong are relatively small for local earthquakes compared to regional earthquakes with C.S.O., Shillong as the reference station. The characteristics of the epicentral variations particularly in the Shillong plateau are observed to be minimum. Strong correlations of epicentres are observed for both local as well as regional earthquake events.